Formation mechanism of serrated grain boundary caused by different morphologies of γ′ precipitates in GH4742 superalloy - Qiang Tian; Wenwen Zhang; Hucheng Li; Yunlong Liu; Tonggang Lu; Jinhui Du; Xingang Liu; Kaiyao Wang (Journal of Materials Research and Technology)
This study investigates the evolution mechanism of the fan-type γ′ structure and its effect on serrated grain boundary in GH4742 superalloy under different cooling rates. The formation mechanism of the fan-type γ′ structure and the mechanism of serrated grain boundary in GH4742 superalloy are discussed. The results show that as the cooling rate decreases, the size of the fan-type γ′ structure increases, exhibiting significant preferential growth characteristics during the process. When the cooling rate is below 120 °C/h, both the size and the number of the fan-type γ′ structure branches increase sharply. The size grows from 2.5 μm at 120 °C/h to 45.6 μm at 1 °C/h, and the number of branches increases from 7 at 120 °C/h to 40 at 1 °C/h. Furthermore, the fan-type γ′ structure shows different characteristics in terms of serrated grain boundary at various cooling rates. When the cooling rate is higher than 120 °C/h, the fan-type γ′ structure mainly manifests a pinning mechanism, resulting in small amplitude fluctuations of the serrated grain boundary. However, when the cooling rate drops below 120 °C/h, the growth mechanism becomes dominant, leading to larger cellular structures and more twisted serrated grain boundaries. Consequently, as the cooling rate decreases, the amplitude of the serrated grain boundaries increases from 1.4 μm to 50.4 μm, and the wavelength increases from 3.5 μm to 262.5 μm. The findings of this study are of significant importance for the microstructure optimization and performance regulation of GH4742 superalloy.